2010
DOI: 10.1111/j.1476-5381.2009.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol is anti‐inflammatory in BV2 microglial cells by inactivating nuclear factor‐kappaB and inhibiting mitogen‐activated protein kinases

Abstract: Background and purpose:Cilostazol is a specific inhibitor of 3′-5′-cyclic adenosine monophosphate (cAMP) phosphodiesterase, which is widely used to treat ischemic symptoms of peripheral vascular disease. Although cilostazol has been shown to exhibit vasodilator properties as well as antiplatelet and anti-inflammatory effects, its cellular mechanism in microglia is unknown. In the present study, we assessed the anti-inflammatory effect of cilostazol on the production of pro-inflammatory mediators in lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 54 publications
5
75
2
Order By: Relevance
“…Our study only demonstrated expression of TNF-α was upregulated in BV2 cells by apelin. Except for TNF-α, MIP-1α and MCP-1 have been implicated as potential modulators of the acute inflammatory response in the CNS [35]. They have potent chemoattractant capability and promote monocyte recruitment into an inflammatory or pathological site.…”
Section: Discussionmentioning
confidence: 99%
“…Our study only demonstrated expression of TNF-α was upregulated in BV2 cells by apelin. Except for TNF-α, MIP-1α and MCP-1 have been implicated as potential modulators of the acute inflammatory response in the CNS [35]. They have potent chemoattractant capability and promote monocyte recruitment into an inflammatory or pathological site.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical data suggest that PDE3 inhibition therapy given via infusion in heart failure, bypass operations, and enterovirus 71 infection did show antiinflammatory effects (37)(38)(39). During the last decade, a growing number of studies suggest that PDE3 inhibition might be involved in immunosuppression (40)(41)(42)(43)(44)(45)(46)(47)(48), although there is no definitive proof. There have been concerns that PDE3 inhibitors were associated with increased cardiovascular mortality in previous clinical trials (49,50).…”
Section: Introductionmentioning
confidence: 99%
“…Lev., distributed over several Asian countries, has been used for the treatment of pain and fever in Korean traditional medicine [2]. While searching for anti-inflammatory natural products using BV2 microglial cells, which are widely employed in in vitro assay systems [3,4], it was found that an 80 % methanolic extract of S. pseudo-lasiogyne significantly inhibited NO production induced by lipopolysaccharide (LPS) in BV2 microglial cells. Thus, we attempted to isolate active compounds from S. pseudo-lasiogyne and to evaluate those compoundsʼ anti-inflammatory activity in BV2 microglia.…”
mentioning
confidence: 99%